The Role of Four-wheeled Patrol in Preventing Motor Vehicle Theft - Andik Wiratika (Indonesian Journal of Police Studies, 2020)
This research is motivated by the high number of vehicle theft cases against other acts in the Karawang district police jurisdiction. The National Police need to take patrol actions to avoid meeting advocacy intentions and opportunities, specifically in the mix. Therefore, the purpose of this study is to describe the general description of motor vehicle theft and the role of four-wheeled patrols as well as the challenge factors that influence the role of four-wheeled patrol units in the Satsabhara Patrol Unit on preventing motor vehicle theft. The research used is descriptive qualitative with field research. Data sources include primary data and secondary data collected by interview techniques, participant observation, and documentation. Data validity is through the source triangulation technique, while data analysis is based on interactive data analysis. Knife analysis is based on role theory, management theory, and crime prevention theory. The results of the study concluded that the crime of two-wheeled motor vehicle theft (R2) ranks highest compared to other crimes in the Karawang district police jurisdiction. Four-Wheeled Patrol Activities (R4) Sabhara Unit Patrol Unit of the Karawang Regional Police conducted based on Operational Procedure Standards (SOP), divided into 3 (three) for preparation, implementation, and termination as well as in every monitoring activity. Four-Wheel Patrol (R4) Patrol Unit Sabhara Police Karawang has agreed to management principles, namely planning, organizing, budgeting and implementation, as well as supervision and improvement, have also been supported by the rules of the role according to expectations, norms, the form of relations with what they are and punishment. The role of consideration is done through social, asking situational, and accessing the community/community. Factors that hamper the role of empathy wheel patrol (R4) are the limited number of member patrols, limited fuel budget, and the less active community in helping police duties. Therefore the suggestion of this research is the need to further enhance cooperation with the community both with community groups, so that special public order security vehicle theft can be prevented as early as possible.